A Response Surface Methodology to Optimize the Vield of Alkyd Resin from Jatropha (Jatropha Curcas) and Sesame (Sesamum İndicum) Seed Oils Using CaCO3 as Catalyst - Mustapha, Aliru Olajide; Oladele, Simeon Gbenga; Adisa, Salihu Folorunsho; Afolabi, Yemisi Tokunbo (Fırat University, 2022)
The low-cost feedstocks such as sesame (sesamum indicum) and jatropha (jatropha curcas) seed oils were utilized to optimize the yield of alkyd resins. The experimentally selected input factors ranges in the molar ratios of oil:glycerol (0.3 – 1), phythalic anhydride: glycerol (1 – 3), and catalyst (0.5–1.5 wt. %) for optimization were established using the response surface methodology (RSM) of Box Behken model to improve the alkyd resin yield factors. The optimization solution utilizing CaCO3 catalysts, and a combination of other process factors evaluated, as well as the corresponding desirability functions, was found using analysis of variance (ANOVA) results for refined sesame alkyd resin (RSAR) and refined jatropha alkyd resin (RJAR). The RSAR optimization using a CaCO3 concentration of 1.5 wt. % at a molar ratios of oil:glycerol (1.0:1.0) and phythalic anhydride:glycerol (3.0:1.0), while the RJAR at a similar catalyst concentration of 1.5 wt. %, molar ratio of oil:glycerol (1.0:1.0), and phythalic anhydride:glycrol (2.8:1.0) were observed for the alkyd resin optimization for the two processes. At these reaction conditions, the predicted and experimental biodiesel yield were 48.26 % and 47.29 % for RSAR and 62.07 % and 61.61 % for RJAR, respectively which shows less than 0.5% variations in both cases.